Physical inactivity in nine European and Central Asian countries: an analysis of national population-based survey results. (18th August 2021) - Whiting, Stephen; Mendes, Romeu; Abu-Omar, Karim; Gelius, Peter; Crispo, Anna; McColl, Karen; Simmonds, Phillipa; Fedkina, Natalia; Andreasyan, Dianne; Gahraman, Hagverdiyev; Migal, Tatyana; Sturua, Lela; et al.
Abstract: Background: Physical inactivity is a major risk factor for non-communicable diseases. However, recent and systematically obtained national-level data to guide policy responses are often lacking, especially in countries in Eastern Europe and Central Asia. This article describes physical inactivity patterns among adults in Armenia, Azerbaijan, Belarus, Georgia, Kyrgyzstan, Republic of Moldova, Tajikistan, Turkey and Uzbekistan. Methods: Data were collected using the Global Physical Activity Questionnaire drawing nationally representative samples of adults in each country. The national prevalence of physical inactivity was calculated as well as the proportional contribution to total physical activity (PA) during work, transport and leisure-time. An adjusted logistic regression model was applied to analyze the association of age, gender, education, household status and income with physical inactivity. Results: National prevalence of physical inactivity ranged from 10.1% to 43.6%. The highest proportion of PA was registered during work or in the household in most countries, whereas the lowest was during leisure-time in all countries. Physical inactivity was more likely with older age in eight countries, with female gender in three countries, and with living alone in three countries. There was no clear pattern of association with education and income. Conclusion: Prevalence of physical inactivity is heterogeneous across the region. PA during leisure-time contributes minimally to total PA in all countries. Policies and programs that increase opportunities for active travel and leisure-time PA, especially for older adults, women and people living alone will be an essential part of strategies to increase overall population PA.